Terrain‐inclination‐based Three‐dimensional Localization for Mobile Robots in Outdoor Environments. Issue 3 (27th March 2014) - Zhu, Xiaorui; Qiu, Chunxin; Minor, Mark A.
<x xml:space="preserve">Abstract</x> A new terrain‐inclination‐based localization technique is proposed in this paper to enable a robot to identify its three‐dimensional location relative to measurable terrain inclinations. Given a topographical map and a planned path, a robot‐terrain‐inclination model (RTI model) is extracted along the path on the terrain upon which the robot is operating. A particle filter is then used to fuse the measurement data with the robot motion based on the extracted RTI model for either a three‐wheeled or a four‐wheeled mobile robot. Experiments were carried out in four outdoor scenarios: one short path with different initial conditions and map resolution, another short path with different surface roughness and sensor accuracy, and two long paths with different types of rigid terrains and multiple loops. Experimental results show that the proposed method could achieve good localization performance on inclined outdoor terrains.